If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) = (3 + -1x) Reorder the terms: 5(3 + x) = (3 + -1x) (3 * 5 + x * 5) = (3 + -1x) (15 + 5x) = (3 + -1x) Remove parenthesis around (3 + -1x) 15 + 5x = 3 + -1x Solving 15 + 5x = 3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 15 + 5x + x = 3 + -1x + x Combine like terms: 5x + x = 6x 15 + 6x = 3 + -1x + x Combine like terms: -1x + x = 0 15 + 6x = 3 + 0 15 + 6x = 3 Add '-15' to each side of the equation. 15 + -15 + 6x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + 6x = 3 + -15 6x = 3 + -15 Combine like terms: 3 + -15 = -12 6x = -12 Divide each side by '6'. x = -2 Simplifying x = -2
| .6(g+3)=-2(g+31) | | 24+3x=-45 | | .4x^2-1.1x=2 | | (2x^2+9x+4)=0 | | P+5=17 | | -4/5x-17=-10/3x-55 | | -14.4=-.6p | | 2x+10=x+0 | | 160/4= | | x^2+17X+49-3x=0 | | 21.5+.5x=50 | | X-3-15=12 | | 5x-(6x+2)=5x-20 | | X/3+2=9+4 | | -6x-4y=21 | | 2x-8=4y | | 180/3= | | 10x^2=11x+35 | | (5t+3)-2*(t+3)=29-5t | | 14y^2-19y+4=11y^2+11y-5 | | 6f-2=6f-2 | | 3/4=n | | -7-26=n | | 8p+6-7p= | | y^2-9y+15=0 | | 4-x=5x+28 | | 2(2x+22)=8x-20 | | 5q+4q= | | 6y-10=0 | | 14+8x=32+8x | | 2x=60-5x | | m-6/5+3.8=7-2m |